Taking stock of the social determinants of health: A scoping review. - Kelsey Lucyk; Lindsay McLaren (PLoS ONE)
Background In recent decades, the social determinants of health (SDOH) has gained increasing prominence as a foundational concept for population and public health in academic literature and policy documents, internationally. However, alongside its widespread dissemination, and in light of multiple conceptual models, lists, and frameworks, some dilution and confusion is apparent. This scoping review represents an attempt to take stock of SDOH literature in the context of contemporary population and public health. Methods We conducted a scoping review to synthesize and map SDOH literature, informed by the methods of Arksey and O'Malley (2005). We searched 5 academic and 3 grey literature databases for "social determinants of health" and "population health" or "public health" or "health promotion," published 2004-2014. We also conducted a search on "inequity" or "inequality" or "disparity" or "social gradient" and "Canad*" to ensure that we captured articles where this language was used to discuss the SDOH. We included articles that discussed SDOH in depth, either explicitly or in implicit but nuanced ways. We hand-searched reference lists to further identify relevant articles. Findings Our synthesis of 108 articles showed wide variation by study setting, target audience, and geographic scope, with most articles published in an academic setting, by Canadian authors, for policy-maker audiences. SDOH were communicated by authors as a list, model, or story; each with strengths and weaknesses. Thematic analysis identified one theme: health equity as an overarching and binding concept to the SDOH. Health equity was understood in different ways with implications for action on the SDOH. Conclusions Among the vast SDOH literature, there is a need to identify and clearly articulate the essence and implications of the SDOH concept. We recommend that authors be intentional in their efforts to present and discuss SDOH to ensure that they speak to its foundational concept of health equity.